Antibacterial Activity of Green-Synthesized Zinc Oxide Nanoparticles from Ganoderma lucidum Mushroom Extract Against Multidrug-Resistant Bacteria: An in Vitro Study - Kareem, Hasan Jamal; Al-Araji, Alaa Mohsin (Iraqi Journal of Science, 2026)
The green synthesis of nanoparticles is regarded as an eco-friendly, cost-effectiveness, and simple methodology. Using green synthesis techniques for nanoparticles may enhance the characteristics of these nanomaterials through reduced dimensions and specific shapes achieved. Ganoderma lucidum mushroom has numerous bioactive compounds, such as proteins, polysaccharides, and secondary metabolites, which can act as reducing and stabilizing agents in nanoparticles synthesis. The antibacterial activity of zinc oxide nanoparticles (ZnO-NPs) has received considerable interest due to their ability to interact with bacterial surfaces and penetrate the bacterial core, hence revealing unique bactericidal mechanisms. This study explores the green synthesis of ZnO-NPs using G. lucidum extract as a reducing agent. The fruiting bodies powder was extracted with hot water in a shaking water bath at 75 °C with 40 rpm for 2 hours, then filtered to obtain G. lucidum aqueous extract. The nanoparticles, synthesized by reacting zinc chloride salt with the extract, were characterized using UV, FTIR, AFM, EDX, and FESEM. The antibacterial activity of ZnO-NPs was evaluated using the agar well diffusion method. The characterization techniques confirmed the successful biosynthesis of ZnO-NPs, revealing a diameter of 44.62 nm, and the particles formed were spherical, hexagonal, and triangular. Antibacterial activity was tested against four MDR bacterial strains (Staphylococcus aureus, Enterococcus faecalis, Pseudomonas aeruginosa, and Escherichia coli), showing significant efficacy. The highest inhibition zone (23.333 mm) was observed for S. aureus at a ZnO-NPs concentration of 100 mg/ml. This finding has significance in revealing an eco-friendly antibacterial agent as an alternative to conventional antibiotics.